2016
DOI: 10.1016/j.toxrep.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolomic profiling indicates structure-based perturbations in serum phospholipids in children with acetaminophen overdose

Abstract: Phospholipids are an important class of lipids that act as building blocks of biological cell membranes and participate in a variety of vital cellular functions including cell signaling. Previous studies have reported alterations in phosphatidylcholine (PC) and lysophosphatidylcholine (lysoPC) metabolism in acetaminophen (APAP)-treated animals or cell cultures. However, little is known about phospholipid perturbations in humans with APAP toxicity. In the current study, targeted metabolomic analysis of 180 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…As known, activation charcoal can significantly reduce the overall drug absorption when given shortly and works in patients suffering from acute overdose such as organochlorine insecticides and herbicides [ [39] , [40] , [41] ]. Moreover, it can be used in gastrointestinal decontamination overdose of drugs and toxins, reducing their absorption [ 39 , 42 ]. The oral route is the most common type of exposure reported in the current study ( Table 4 ), and the possible reason is that patients in the age group of 1–5 years were accidental toxicity of drugs or chemicals were the most cases reported [ 30 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As known, activation charcoal can significantly reduce the overall drug absorption when given shortly and works in patients suffering from acute overdose such as organochlorine insecticides and herbicides [ [39] , [40] , [41] ]. Moreover, it can be used in gastrointestinal decontamination overdose of drugs and toxins, reducing their absorption [ 39 , 42 ]. The oral route is the most common type of exposure reported in the current study ( Table 4 ), and the possible reason is that patients in the age group of 1–5 years were accidental toxicity of drugs or chemicals were the most cases reported [ 30 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Attention was paid principally to their links to the DILI and not to the drug causing the event. Among them, few studies addressed the identification of specific markers for DILI prediction or individual susceptibility determination [43,47,[74][75][76] while the vast majority were focused on DILI diagnosis and follow-up [55,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95].…”
Section: Metabolites Identified As Putative Biomarkers Of Dili In Humansmentioning
confidence: 99%
“…Phospholipids are important components of the cellular membranes, and they regulate cell functions as signalling molecules. Several of the studies reviewed reported increased or decreased levels of different phospholipids, or changes in their specific structural properties [74,75,79,82,83,[88][89][90][91]. It is possible that these changes might be related to the access or insertion process of the phospholipids to the membrane bilayers during hepatic regeneration.…”
Section: Metabolites Identified As Putative Biomarkers Of Dili In Humansmentioning
confidence: 99%
“…Bhattacharyya et al showed the presence of PCs and lysoPCs with very long fatty acids significantly decreased in overdose conditions indicative of a structure-activity relation with enzymes responsible for phospholipid metabolism. 30 Recently, Yamada et al…”
Section: Introductionmentioning
confidence: 99%